2012
DOI: 10.3758/s13414-011-0255-y
|View full text |Cite
|
Sign up to set email alerts
|

Context effects on tempo and pleasantness judgments for Beatles songs

Abstract: Context effects on tempo and pleasantness judgments of different tempos were demonstrated in three experiments using Beatles songs. In Experiments 1 and 2, we explored how listening to versions of the same song that were played at different tempos affected tempo and pleasantness ratings. In both experiments, contrast effects were found on judgments of tempo, with target tempos rated faster when context tempos were slow than when they were fast. In both experiments, we also showed that the peak of the pleasantn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…These results parallel data drawn from the perception literature; people generally choose slightly slower tempi of fast examples and slightly faster tempos for slow examples (Geringer, 2010; Rashotte & Wedell, 2012, 2014; Yarbrough, 1987). Compared with the listening preference responses in Study 1 for faster examples, tapping performance results were parallel for “Chaconne”; participants in both groups tapped faster than the baseline tempo.…”
Section: Studysupporting
confidence: 81%
See 1 more Smart Citation
“…These results parallel data drawn from the perception literature; people generally choose slightly slower tempi of fast examples and slightly faster tempos for slow examples (Geringer, 2010; Rashotte & Wedell, 2012, 2014; Yarbrough, 1987). Compared with the listening preference responses in Study 1 for faster examples, tapping performance results were parallel for “Chaconne”; participants in both groups tapped faster than the baseline tempo.…”
Section: Studysupporting
confidence: 81%
“…Results agree with extant literature; a regression to more moderate tempi was demonstrated by most participants (cf. Geringer, 2010; Rashotte & Wedell, 2012, 2014). Participants in Study 2 who provided tapping wanted slow examples to be faster and fast examples to be slower.…”
Section: Studymentioning
confidence: 99%
“…The unidimensional representation implies that stimuli at opposite ends of the dimension are mutually exclusive, such that any degree of pleasantness is assumed to preclude unpleasantness and vice versa (Russell and Carroll, 1999), a proposal that has also received experimental support from several behavioral studies (Harris, 1929;Carroll et al, 1999;Zellner et al, 2003Zellner et al, , 2006Rashotte and Wedell, 2012). Our findings showing stronger correlations between ensemble patterns for perceptually similar odors, which decrease monotonically for perceptually dissimilar odors, imply that unpleasant and pleasant valence cannot coexist (be represented simultaneously) in the amygdala at the level of fMRI ensemble codes because pattern overlap of these two valence extremes would obscure their unique content.…”
Section: Discussionmentioning
confidence: 99%
“…They found that perceived pleasantness followed a singlepeaked function, with moderate tempi rated as the most pleasant while extremely fast and extremely slow tempi were rated the least pleasant. This single-peaked form was found across contexts and song familiarity levels, although the peak of the function shifted with tempo context and this shift was reduced for the more familiar songs (Rashotte & Wedell, 2012, 2014. There are several methodological differences between the Webster and Weir (2005) and Wedell (2012, 2014) studies, but a key difference may be in the measure of valence.…”
mentioning
confidence: 89%
“…The focus of the present study was on musical tempo, which can be digitally altered with minimal disturbance to other features of the music (Rashotte & Wedell, 2012) and which has implications for behavioral and physiological effects. Our study is based upon the theory of core affect (Russell & Barrett, 1999), according to which affective responses vary primarily along two dimensions.…”
mentioning
confidence: 99%